2015
DOI: 10.1002/asmb.2115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two algorithms for solving a two‐stage bilinear stochastic programming problem with quantile criterion

Abstract: The paper is devoted to solving the two-stage problem of stochastic programming with quantile criterion. It is assumed that the loss function is bilinear in random parameters and strategies, and the random vector has a normal distribution. Two algorithms are suggested to solve the problem, and they are compared. The first algorithm is based on the reduction of the original stochastic problem to a mixed integer linear programming problem. The second algorithm is based on the reduction of the problem to a sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In the following theorem, it is shown that the optimization problems (4) and (15)- (20) are equivalent in the following sense [17]:…”
Section: An Equivalent Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…In the following theorem, it is shown that the optimization problems (4) and (15)- (20) are equivalent in the following sense [17]:…”
Section: An Equivalent Problemmentioning
confidence: 99%
“…is an optimal solution of problem (15)-(20); 2. for every optimal solution ( , u, y 1 , … , y N , 1 , … , N , 1 , … , N ) of problem (15)- (20), there exists y(⋅) such that (u, y(⋅)) is an optimal solution of problem (4); 3. the optimal objective function values of problems (4) and (15)- (20) are equal, and they are attained simultaneously in both problems; 4. if the optimal objective function values of problems (4) and (15)- (20) are not attained, then minimizing sequences of the variable u of both problems coincide.…”
Section: An Equivalent Problemmentioning
confidence: 99%
See 3 more Smart Citations